Evidence of reproductive isolation confirms that Apis andreniformis (Smith, 1858) is a separate species from sympatric Apis florea (Fabricius, 1787). - Wongsiri, S.; Limbipichai, K.; Tangkanasing, P.; Mardan, Makhdzir; Rinderer, T.; Sylvester, H. A.; Koeniger, G.; Otis, G. (Elsevier, 1990)
The species Apis andreniformis (Smith, 1858), the small dwarf honey bee of South-east Asia, is recognized as a valid biological species. This recognition is based on distinctive endophallus characteristics in comparison with sympatric Apis florea (Fabricius, 1787). Additionally, scanning electron microscope images of drone basitarsi are presented, as are preliminary comparisons of wing venation.